Qualidade de vida relacionada à saúde do enfermeiro a partir da terceira idade - Pinheiro, Thalison Fernandes (2019)
Health-related quality of life (HRQoL) is linked to the individual's perception (personal experience, beliefs, expectations) about their physical, psychological and social conditions, whether or not they are affected by dysfunctions, whether by diseases, treatments and other diseases. Investigating this phenomenon in nursing becomes relevant due to the characteristics of the work itself, which may have repercussions on workers' health and often impacting their quality of life. Thus, the question was how is the HRQoL of nurses in the elderly? This study aimed to evaluate the health-related quality of life of nurses from the elderly living in the city of Cuiabá-MT. This is a cross-sectional study of a quantitative approach, with professional nurses in the elderly, located through the registration in the Regional Nursing Council (COREn), granted through the consent term for research purposes only. Data collection took place in the second half of 2018, ending in the first quarter of 2019. Data were collected through two instruments, the first sought to delineate the sociodemographic profile, professional history, and health habits, while the second used was the The Medical Outcomes Study 36-item Short- Form Health Survey (SF-36) to measure individuals' HRQoL. The Ethics Committee on Research with Human Beings approved the project, with the opinion 2,670,711. The obtained data were tabulated by means of the absolute (n) and relative (%) frequency arranged in tables. The Shapiro-Wilk test was performed to verify the normality of the data, and after finding the non-normality, the nonparametric Kruskal-Wallis median test was performed. When the Kruskal-Wallis test was significant (p <0.05), the Conover-Iman test was performed for the multiple comparison between the medians. Among the results, it was evidenced that the participants of this study, most are female, heads of families and are still in professional practice and many of them experienced the situation of multi-employment, with weekly workload over 60 hours, beyond social responsibilities as mother and wife. All these functions and activities arising from social relations may have contributed to an overload, burnout and to the development of chronic diseases, and consequently the use of continuous medication. Physical limitation was also observed, where overweight became prevalent and the identification of occupational diseases in the workplace, factors that may contribute to new health and quality of life implications. A mean HRQOL score of 74.45 was found, and when domains were assessed in isolation, the lowest mean in the general health state domain was 65.41, and the best average, 80.26, for social aspects. Finally, it was concluded that in the literature, nurses from the old age have a better HRQoL compared to those who are in professional practice because they are not in contact with the characteristic factors of their profession.